ANALYSIS OF MARGIN RATES IN MURABAHAH SMALL BUSINESS CREDIT FINANCING AT BANK ACEH SYARIAH KCP UIN AR-RANIRY BANDA ACEH, INDONESIA - Auni Alwafi; T.Surya Reza (JURISTA: Jurnal Hukum dan Keadilan, 2025)
This study aims to analyse the effect of financing tenure on the determination of margin rates in the murabahah financing scheme for the People’s Business Credit (KUR) product at Bank Aceh Syariah KCP UIN Ar-Raniry, as well as to examine its legal implications from the perspective of Islamic economic law. The research employs a normative-empirical approach with a qualitative descriptive method. Primary data were collected through interviews with credit analysts at Bank Aceh Syariah, while secondary data were obtained from official documents, legal literature, and Islamic banking regulations. The findings indicate that the financing margin rate increases proportionally with the length of the financing period as compensation for the bank’s risk; however, margin determination is conducted internally, with limited room for customer negotiation. Furthermore, the determination of financing tenure has not fully considered the customers' ability in a participatory manner, which potentially leads to injustice in the murabahah contract. Islamic economic law emphasises the importance of justice (ʿadl), transparency of information, and mutual consent (tarāḍin) to ensure that financing contracts comply with the maqāṣid al-sharī‘ah. This study recommends enhancing transparency and customer involvement in the margin and tenure determination process to ensure that Islamic financing operates effectively and benefits all parties involved.